Síntese e caracterização de Zeólita NaY - Viana, Andressa (2017)
Zeolites are microporous crystalline materials with three-dimensional structure composed of [SiO4]4- and [AlO4]5-. The synthesis of zeolites has been widely researched because its application is very large due to its numerous properties. Its synthesis is of low cost, being part of the class of adsorbentes ionic exchangers. They are widely used in heterogeneous catalysis and also as adsorbents in various processes, for example, application in heavy metal removal processes, due to its microporous structure with multidimensional channel systems that allow the exchange of ions between these cavities. Thus, the objective of this work was to synthesize zeolites of the NaY type using sodium aluminate and colloidal silica by means of a hydrothermal treatment, being verified the influence of temperature and time. The structure of the obtained material was characterized by scanning electron microscopy coupled to a power dispersion spectrometer (SEM-EDS), X-ray diffraction (XRD), N2 adsorption / desorption analysis and transformed Infrared spectroscopy of Fourier (FTIR). Zeolites synthesized at 24 and 48 hours at 80°C showed a similar morphological pattern, with polyhedral shapes closer to those of commercial zeolite. It was found that the values of the Si/Al ratio were close to 1,5, a characteristic value for zeolite of type Y. They showed good crystallinity observed by the diffractograms of the samples NaY 1 and NaY 6, showing the characteristic peak in 2θ approximately 6°. By the FTIR technique, the bands presented for the different synthesis parameters remained close, evidencing the different vibrations of the TO4 (T = Si or Al) bonds of zeolite. With the textural analysis, by the adsorption/desorption method of N2, it can be concluded that there was a better formation of NaY zeolite with the synthesis carried out mainly in 24h and 80°C.